Etoricoxib Alleviate Depression Like Behavior Induced By Interferon-Α In Mice: Behavioral And Biochemical Indications (International Journal of Food and Nutritional Sciences, 2022)
Interferon-α (IFN-α) administration induces major depression in a significant number of patients undergoing treatment for viral illnesses and other chronic diseases. Non-steroidal anti-inflammatory drugs (NSAIDs) are known to counteract a number of IFN-α induced side effects, including pro-inflammatory cytokine activation and stress hormone release. To investigate this possibility further, we sought to determine the effect of the Etoricoxib on behavioral and biochemical parameters in brain induced by acute IFN-α exposure. Depression was induced by INFα (16 × 105 IU/kg, body weight) for six consecutive days in outbred adult Swiss Albino female mice. The standard anti-depressant drug Amitriptyline (10 mg/kg, orally) and chosen NSAID, Etoricoxib (10 mg/kg, orally) were administered simultaneously and behavioral & biochemical responses were recorded. The study’s findings demonstrated that the selected drug had antidepressant properties comparable to Amitriptyline. Analysis of Open field test data indicated that administration of Etoricoxib induced significant differences in the frequencies of crossing indicated in the number of squares crossed and rearing indicated in the number of rearing instances when compared to the control and vehicle+ IFN-α group. Etoricoxib (ET), produced significant reduction (p